The influence of product quality, service quality and price o customer satisfaction and loyalty at Transmart Padang outlets - Ridho Al Fikri, Muhammad; Wardi, Yunia (Marketing Management Studies, 2024)
The primary aim of this investigation is to examine how to product quality, service quality, and price effect the satisfaction and loyalty of Transmart customers in Padang. The study encompassed 150 customers of Transmart Padang and employed a quantitative descriptive research approach using a probability sampling technique. The study's findings reveal that product quality, service quality, and price significantly impact customer satisfaction. Specifically, both variables related to product quality influence customer satisfaction, while service quality alone does not directly influence customer loyalty. However, the price variable directly impacts customer loyalty. Furthermore, customer satisfaction emerges as a significant determinant of customer loyalty. In the mediation analysis, it was discovered that customer satisfaction server as a mediator between product quality and customer quality. However, it does not mediate the relationship between service quality and customer loyalty. Additionally, customer satisfaction does not demonstrate its role as an intermediary variable between price and customer loyalty.